PENDEKATAN BEHAVIOR DALAM MENANGANI DAMPAK MODEL PEMBELAJARAN BLENDED LEARNING DI MASA PANDEMI COVID-19 TERHADAP PESERTA DIDIK DI SMA MUHAMMADIYAH 2 GENTENG - Lupita Setiawan (SOSIOEDUKASI, 2021)
Behavior is one approach in guidance and counseling to overcome mal-adaptive behavior towards an adaptive attitude. The behavior approach is the right approach to handle blended learning models during the Covid-19 pandemic, so that students are able to carry out their duties well at school, without experiencing obstacles. This undisciplined behavior is influenced by several reasons, including students' private problems as a result of divorce, living with grandmother without parental supervision, and data package constraints. The basis of this paper is a field research that uses a behavioral approach and a descriptive-qualitative method. The results of this study describe several efforts in the counseling process of several students, including reinforcement technique, counseling contracts, homework, and punishment. With the behavior flow stages, the process of changing the attitudes of students who experience the impact of blended learning can be improved and students are able to be adaptive to participate in learning.